Public Services Communication Strategy For The Medan Marelan Camat Office (S-O-R Theory Study) - Dani, Irma; Rasyid, Abdul; Zuhriah (Pena Cendekia Insani, 2022)
The purpose of this study is to determine the communication strategy of public services at the Medan Marelan District Office. This research uses communication theory, communication strategy, public service, and S-O-R theory. This research is a type of qualitative research with a descriptive research design, including data collection, production of oral and written data, and direct data collection from the research location. The main and secondary data sources consist of eight informants. Interviews, observations, and documentation were used for data collection, while the data analysis procedures included data reduction, data presentation, and drawing conclusions. Researchers used triangulation of data, procedures, and time to validate the data. Based on the research results, the public service communication strategy is based on the communicator, communication message, communication media, and the intended audience. The public's reaction to the services provided by the Medan Marelan Village shows that the Medan Marelan Village provides excellent and comprehensive service to the community as service recipients, but indeed there are still a few problems with the timeliness of completing services, this is due to network disturbances or when the lights go out. . However, only one or two of these were found, the rest of the service officers have been very maximal in providing public services.